Pertumbuhan Tanaman Seledri (Apium graveolens L.) dengan Pengaruh Pemberian Air Kelapa Tua pada Media Hidroponik Sistem Wick - Annisyah Tri Putri; Rahmadina Rahmadina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effect of mature coconut water on the growth of celery plants and to identify the most effective concentration. The method used was a Completely Randomized Design (CRD) with four levels of treatment, namely AB mix 15 ml, 250 ml coconut water, 300 ml coconut water, and 350 ml coconut water. The observed parameters included plant height, number of leaves, stem diameter, and chlorophyll content. The results showed, the best result for plant height observed at the 350 ml treatment (19.00 cm). However, for the number of leaves and stem diameter, the 300 ml treatment gave the best results (28.20 leaves and 1.10 cm). Chlorophyll analysis showed a significant effect on chlorophyll B and total chlorophyll, with the highest content found in specific treatment combinations. In conclusion, mature coconut water can be used as an effective natural growth regulator to enhance celery growth in a wick hydroponic system, with optimal concentrations varying depending on the growth parameter observed. Keywords: Coconut Water, Wick Hydroponics, Celery